Manganese levels and hepatocellular carcinoma: A systematic review and meta-analysis based on Asian cohort. Issue 32 (August 2019) - Chen, Xiu-Bing; Wei, Yue-Hui; Chen, Xiu-Ke; Zhong, Jian; Zou, You-Bao; Nie, Jia-Yan
Abstract : Abstract: Several studies have investigated the relationship between Manganese (Mn) levels and hepatocellular carcinoma (HCC), but the results were inconsistent. Thus, we conducted a systematic review and meta-analysis to evaluate the association between Mn levels and HCC. Nine studies focusing on hair Mn levels, 6 studies on serum Mn levels and 6 studies on tissue Mn levels were identified in a systematic search of PubMed, CNKI, Wanfang and SinoMed databases. Standard mean differences (SMD) with the corresponding 95% confidence intervals (CI) were pooled to compare the Mn levels between HCC and controls. In serum, the Mn levels in HCC were significantly lower than in healthy controls (SMD (95% CI): −0.941 (−1.559, −0.323)). In hair, the Mn levels in HCC were slightly lower than in healthy controls, but not significant (SMD (95% CI): −0.168 (−0.766, 0.430)). In tissue, the Mn levels in tumors were significantly lower than in adjacent normal tissues (SMD (95% CI): −4.867 (−7.143, −2.592)). Subgroup analysis showed consistent results. In conclusion, this meta-analysis suggested an inverse association between Mn levels and HCC.